The Category of Diminutives in Lithuanian: From Small to Ironic. Diminutives in Balys Sruoga’s “Forest of the Gods” and its Translation into English - Šeškauskienė, Inesa (Vertimo studijos, 2025)
The paper proposes a new approach to the productive polysemous category of diminutive derivatives in Lithuanian. Drawing on the works of cognitive linguistics, the multiple senses of the diminutive are interpreted with reference to the family-resemblance principle. Small size is treated as the prototypical sense, which gives rise to other senses, such as a short period of time, affection, depreciation, etc. Many senses are motivated by metaphor, metonymy, and other mechanisms. The ironic sense is different in that, in each case, it emerges in context through juxtaposition of propositional and intentional frames. Irony is seen as an extension of any of the above senses. The realisation of the ironic sense is analysed in the first ten sections of the novel “Forest of the Gods” by the Lithuanian writer Balys Sruoga and its translation into English, a language known for its limited inventory of derivational diminutives. In the majority of cases, the English translation seems to favour non-diminutive words.
Keywords: diminutives; Lithuanian; irony; translation into English; “Forest of the Gods” by Balys Sruoga